2007
DOI: 10.1017/s0269964807000046
|View full text |Cite
|
Sign up to set email alerts
|

Ordering Conditional Distributions of Generalized Order Statistics

Abstract: The concept of generalized order statistics was introduced as a unified approach to a variety of models of ordered random variables. The purpose of this article is to establish the usual stochastic and the likelihood ratio orderings of conditional distributions of generalized order statistics from one sample or two samples, strengthening and generalizing the main results in Khaledi and Shaked [15], and Li and Zhao [17]. Some applications of the main results are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 16 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…or exchangeable dependent components, especially k-outof-n systems. For instance, see [1], [8], [9], [10], [12], [13], [15], [21], [22], [24], [26], [27], and [28].…”
Section: Mixture Representations Of Inactivity Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…or exchangeable dependent components, especially k-outof-n systems. For instance, see [1], [8], [9], [10], [12], [13], [15], [21], [22], [24], [26], [27], and [28].…”
Section: Mixture Representations Of Inactivity Timesmentioning
confidence: 99%
“…where Expression (8) indicates that the inactivity time (t − T | T ≤ t) of the system at time t is a mixture of the inactivity time (t − X i,i | X i,i ≤ t) of the order statistics at time t with coefficients β i (t) for i = 1, 2, . .…”
Section: Theorem 8 For Anymentioning
confidence: 99%
“…Recently, Li and Zhao (2008) carried out a stochastic comparison on (1.1) and (1.2) of two (n − k + 1)-out-of-n systems and generalized the main results of Khaledi and Shaked (2006). It is worth mentioning here that Hu et al (2007) and Xie and Hu (2008) discussed conditional ordering of generalized order statistics, which includes (1.1) and (1.2) as special cases and, hence, extends some of the related results.…”
Section: Introductionmentioning
confidence: 75%
“…Kahledi and Shojaei [8] established the analogous comparison results for record values. Hu, et al [6] further obtained several comparison results for generalized order statistics. In particular, they obtained [X k:n − t|X l:n > t] ≤ lr [X k :n − t|X l :n > t]…”
mentioning
confidence: 99%
“…for 1 ≤ l < k ≤ n. Recently, Hu, et al [5] built that [X k:n − t|X l:n > t] ≤ lr [X k+1:n − t|X l:n > t] ( 4 ) for 1 ≤ l < k < n and t ∈ R + , which is an open problem in [6]. From (2), (3), and (4), it can be concluded that, for 1 ≤ l < k ≤ n and t ∈ R + , [X k:n − t|X l:n > t] is increasing in k, and decreasing both in l and n according to the likelihood ratio order.…”
mentioning
confidence: 99%